Bridging Spirituality and Technology: Ethical Integration of Artificial Intelligence in Pesantren Education - Suncaka, Eko (Pascasarjana Universitas KH. Abdul Chalim, 2024)
Pesantren are now confronted with both significant challenges and opportunities in the digital era, particularly with the advent of Artificial Intelligence (AI). This study aims to examine AI’s role as a bridge between spirituality and technology within pesantren, and to identify its potentials, challenges, and implementation strategies that align with pesantren values. Employing a descriptive qualitative methodology, the research analyzes AI applications across several educational dimensions, including personalized learning, administrative efficiency, development of digital and entrepreneurial skills, and decision‐support systems. The findings reveal that AI enhances instructional effectiveness by adapting materials to meet students’ individual needs, streamlines administrative workflows, and fosters edu-technopreneurial ventures. Nonetheless, AI integration encounters ethical and cultural challenges, especially regarding data protection and the preservation of pesantren traditions. Through prudent, ethics-based implementation strategies, AI holds promise for reinforcing pesantren’s mission to cultivate a generation that is technologically proficient without forsaking its spiritual and cultural foundations.